Inorganic-organic room temperature phosphorescent composite material as well as preparation method and application thereof

Through the preparation of inorganic-organic room temperature phosphorescence composites, the problem of unclear boundaries between existing temporary sealing materials and natural teeth is solved, and the labeled luminescent temporary sealing materials with biosafety and high stability is achieved, which simplifies the removal process and reduces natural tooth damage.

CN119505875APending Publication Date: 2025-02-25TIANJIN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411605929.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The boundary between the existing temporary sealing materials and natural teeth is unclear, making it difficult to remove accurately, resulting in damage to natural teeth and has certain biological toxicity to affect the oral environment.

Method used

The inorganic-organic room temperature phosphorescence composite is prepared by a host-guest doping strategy. The material is composed of phosphate and aromatic acid derivatives, which have room temperature phosphorescence luminescence characteristics, and is used in glass ionic hydromensine to form a labelable luminescence temporary sealing material.

Benefits of technology

A markerable luminescent temporary sealing material with high stability is achieved, which can emit obvious phosphorescence after ultraviolet light, forming a clear contrast with natural teeth, simplifying the removal process of temporary sealing material and reducing damage to natural teeth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505875A_ABST
    Figure CN119505875A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of room-temperature luminescent materials, in particular to an inorganic-organic room-temperature phosphorescent composite material as well as a preparation method and application thereof. The room-temperature phosphorescent composite material can be prepared by mixing and heating phosphate and aromatic acid derivatives for a certain time. The preparation method disclosed by the invention is simple to operate, and the obtained phosphorescent composite material is excellent in luminescent property, safe and non-toxic, and can be used as a characteristic luminescent material in marked luminescent temporary sealing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of room temperature luminescent materials, and in particular relates to a room temperature phosphorescent composite material, and a preparation method and application of the room temperature phosphorescent composite material. Background Art

[0002] Room temperature phosphorescent materials have become one of the important research directions in the field of luminescent materials due to their advantages such as long life, large Stokes shift value, color tunability and easy detection. Host-guest doping plays an important role in RTP luminescence. The rigid host environment can limit the movement of guest luminescent molecules, and host-guest doping mainly involves non-covalent interactions, such as weak intermolecular interactions such as hydrogen bonds and electrostatic interactions, which can avoid complex synthetic routes, thus facilitating the large-scale preparation of high-performance RTP materials. Room temperature phosphorescent materials can be applied to optical labeling materials and have broad application prospects in medical diagnosis, biological imaging and other fields, such as immunochromatography technology, monitoring cell activities in living organisms, and optical imaging of specific living tissues. Due to the superior optical labeling properties of room temperature phosphorescent materials, a markable dental temporary sealing material can be developed for use in oral clinical work.

[0003] Temporary dental sealing materials, referred to as temporary sealing materials, are mainly used for temporary sealing of working areas such as caries, pulp disease and periapical disease, and are completely removed before permanent restoration. They are an indispensable part of oral clinical work, especially dental endodontic clinical work.

[0004] During root canal treatment, temporary sealing materials must be completely removed before new temporary sealing materials or permanent restorations can be inserted. The performance of temporary sealing materials will have a significant impact on the effect of clinical treatment. In clinical work, temporary sealing materials under existing technologies mainly have the following problems:

[0005] 1) Clinically, it is required to minimize damage to healthy natural teeth during tooth restoration (see: J.Am.Dent.Assoc, 1990, 120(5):558-566), and to avoid temporary sealing materials from damaging the hardness of dentin, thereby weakening the fracture resistance of teeth and reducing the effectiveness of root canal treatment (see: Wear, 2006, 261(9):980-986; J.Am.Dent.Assoc, 2008, 139(6):751-758.). However, since the color of temporary sealing materials is very similar to that of natural teeth, how to completely remove temporary sealing materials in the oral environment without excessively damaging natural teeth has become an important problem that troubles dentists, and there is currently no perfect solution.

[0006] 2) Some reported fluorescent temporary sealing materials usually contain rare earth metal elements (see: CN 112426367A, 2021.03.02), which have certain biological toxicity and may affect the oral environment (see: Chemosphere, 2017, 181: 55-62; Biomacromolecules, 2019, 20 (9): 3233-3241). In addition, the incident light source will affect the naked eye's observation of the light emitted by the material, making it difficult to distinguish the boundary between the temporary sealing material and the natural tooth body, limiting its clinical application. Summary of the invention

[0007] The purpose of the present invention is to solve the problems that the boundary between existing temporary sealing materials and natural teeth is unclear, it is difficult to remove accurately and thus damages natural teeth, and the existing temporary sealing materials have certain biological toxicity that affects the oral environment, and to provide an inorganic-organic room temperature phosphorescent composite material and its preparation method and application. The present invention uses a host-guest doping strategy to prepare a room temperature phosphorescent composite material, which is a markable luminescent temporary sealing material with both biological safety and high stability.

[0008] The technical solution of the present invention:

[0009] An inorganic-organic room temperature phosphorescent composite material is an inorganic-organic composite solid powder with room temperature phosphorescent luminescence characteristics, which is composed of phosphate and aromatic acid derivatives. The weight percentage content of the organic aromatic acid derivatives ranges from 0.01% to 50%.

[0010] The phosphate includes a phosphate main body and a hydrate composed of the phosphate main body. The phosphate main body is composed of anions and cations, wherein the cations are one or more of the first, second and third main group metals, and the anions are H2PO4 - , or One or more of .

[0011] The aromatic acid derivatives are one or more of the following aromatic acid derivatives:

[0012]

[0013] R1, R2, R3, R4 = OH, OR, NH2, NH-R, wherein the R group is a C1-C8 alkyl group.

[0014] The present invention also provides a method for preparing the room temperature phosphorescent composite material, comprising the following steps:

[0015] (1) Weighing a phosphate and an aromatic acid derivative, and uniformly mixing them to obtain a precursor solid powder;

[0016] (2) The room temperature phosphorescent composite material can be prepared by heating the precursor solid powder and then cooling it to room temperature.

[0017] In some preferred embodiments, the mass ratio of the phosphate to the aromatic acid derivative is 1:1 to 10000:1, more preferably 5:1 to 1000:1.

[0018] In some preferred embodiments, the heating temperature is 50°C to 500°C, more preferably 70°C to 300°C.

[0019] In some preferred embodiments, the heating time is 0.1 min to 600 min, more preferably 0.5 min to 60 min.

[0020] The invention also provides application of the room temperature phosphorescent composite material.

[0021] The application of the room temperature phosphorescent composite material is: using the room temperature phosphorescent composite material as a characteristic luminescent material in a markable luminescent temporary sealing material for oral clinical work.

[0022] Specifically, the application method of the markable luminescent temporary sealing material includes the following steps:

[0023] (1) weighing a room temperature phosphorescent composite material and a glass ionomer cement powder, the main components of which are: 20 to 25 parts by weight of silicon oxide, 20 to 30 parts by weight of calcium fluoride, 10 to 15 parts by weight of sodium fluorosilicate, 20 to 25 parts by weight of aluminum oxide, and 10 to 15 parts by weight of aluminum phosphate, and uniformly mixing them to obtain a precursor solid powder;

[0024] (2) Add glass ionomer cement liquid to the precursor solid powder, the main components of which are: 10 to 30 parts by weight of polyacrylic acid, 5 to 10 parts by weight of tartaric acid, and 20 to 60 parts by weight of deionized water, and mix well to obtain a markable luminescent temporary sealing material.

[0025] In some preferred embodiments, the mass ratio of the room temperature phosphorescent composite material to the glass ionomer cement powder is 1:29 to 29:1, and more preferably 1:19 to 19:1.

[0026] In some preferred embodiments, the mass ratio of the precursor solid powder to the glass ionomer cement liquid is 1:2 to 4:1, more preferably 1:1 to 4:1.

[0027] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention. (In the following specific embodiments, the various technical solutions can be combined with each other in principle to obtain new technical solutions, which should also be regarded as specifically disclosed in the present invention.)

[0028] Advantages and beneficial effects of the present invention:

[0029] 1. The present invention discloses an inorganic-organic room temperature phosphorescent material and a preparation method thereof. The material is prepared by doping an inorganic substance with an aromatic acid derivative and then heating it. The preparation method is simple to operate, and the obtained phosphorescent composite material has excellent luminescent properties, low cost, and good application prospects.

[0030] 2. The present invention also discloses a markable dental temporary sealing material used in oral clinical work and a preparation method thereof. The temporary sealing material is prepared by adding an inorganic-organic room temperature phosphorescent material to glass ionomer cement and then mixing it with resin. The obtained temporary sealing material is safe and non-toxic, and the preparation method is simple and easy to promote. Teeth filled with the temporary sealing material have no obvious difference from conventional temporary sealing materials during daily use, but after ultraviolet light irradiation, the restoration can emit obvious phosphorescence, which forms a clear contrast with natural teeth. In the process of removing the temporary sealing material, it can be effectively distinguished from natural teeth, so as to protect natural teeth and reduce damage to natural teeth under the premise of completely removing the prosthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Delayed emission spectra of the room temperature phosphorescent composite materials prepared in Examples 1-12 of the present invention, (a) is the delayed emission spectrum of Example 1-3, (b) is the delayed emission spectrum of Example 4-6, (c) is the delayed emission spectrum of Example 7-9, and (d) is the delayed emission spectrum of Example 10-12. The spectra show the phosphorescence emission wavelength and phosphorescence quantum yield of Examples 1-12.

[0032] Figure 2 The figures are comparison graphs of the lifetime decay curves of the room temperature phosphorescent composite materials prepared in Examples 1-12 of the present invention, (a) is a comparison graph of the lifetime decay curves of Examples 1-3, (b) is a comparison graph of the lifetime decay curves of Examples 4-6, (c) is a comparison graph of the lifetime decay curves of Examples 7-9, and (d) is a comparison graph of the lifetime decay curves of Examples 10-12. The comparison graphs show the phosphorescence lifetimes of Examples 1-12.

[0033] Figure 3 This is a diagram showing the application effect of the markable luminescent temporary sealing material prepared in Application Example 1 of the present invention in dental clinical work. The diagram shows that in Application Example 1, the boundary between the present invention and the natural tooth is obvious in clinical work.

[0034] Figure 4 This is the delayed emission spectrum of the markable luminescent temporary sealing material prepared in Application Examples 1-5 of the present invention. The spectrum shows the phosphorescence emission wavelength and phosphorescence quantum yield of Application Examples 1-5.

[0035] Figure 5 This is a mechanical property diagram of the markable luminescent temporary sealing material prepared in Application Examples 1-5 of the present invention, which shows the compressive strength of Application Examples 1-5.

[0036] Figure 6 The cell activity test results of the labelable luminescent temporary sealing material prepared in Application Example 1 of the present invention show that DRCs with different SMSED contents have no obvious toxicity to cells when incubated for 1, 2, and 3 days, and the survival rates of the corresponding cells are all above 90%. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It is necessary to point out here that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0038] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0039] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0040] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0041] [Example 1]

[0042] Weigh 700 g of magnesium dihydrogen phosphate and 1 g of terephthalamide, mix them evenly to obtain solid powder. Heat the powder at 220° C. for 15 min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 424 nm, the phosphorescence lifetime is 1.28 s, the phosphorescence quantum yield can reach 75.87%, and it is very easy to observe in a dark environment.

[0043] [Example 2]

[0044] Weigh 1000g of aluminum dihydrogen phosphate and 1g of terephthalic acid, mix them evenly to obtain solid powder. Heat the powder at 220°C for 15min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 427nm, the phosphorescence lifetime is 0.34s, the phosphorescence quantum yield can reach 18.87%, and it is easy to observe in a dark environment.

[0045] [Example 3]

[0046] Weigh 700g of calcium dihydrogen phosphate and 1g of terephthalic acid monoamide, mix them evenly to obtain solid powder. Heat the powder at 180°C for 20min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 430nm, the phosphorescence lifetime is 0.41s, the phosphorescence quantum yield can reach 54.58%, and it is very easy to observe in a dark environment.

[0047] [Example 4]

[0048] Weigh 1000g of magnesium dihydrogen phosphate and 1g of terephthalamide, mix them evenly to obtain solid powder. Heat the powder at 300°C for 5 minutes and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 424nm, the phosphorescence lifetime is 1.19s, the phosphorescence quantum yield can reach 44.55%, and it is very easy to observe in a dark environment.

[0049] [Example 5]

[0050] Weigh 450g of sodium dihydrogen phosphate, 450g of calcium dihydrogen phosphate and 3g of isophthalamide, and mix them evenly to obtain solid powder. Heat the powder at 300°C for 5min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 424nm, the phosphorescence lifetime is 0.30s, the phosphorescence quantum yield can reach 20.48%, and it is easy to observe in a dark environment.

[0051] [Example 6]

[0052] Weigh 1000g of calcium monohydrogen phosphate and 20g of terephthalic acid, mix them evenly to obtain solid powder. Heat the powder at 500°C for 5 minutes and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 427nm, the phosphorescence lifetime is 0.22s, the phosphorescence quantum yield can reach 11.99%, and it is easy to observe in a dark environment.

[0053] [Example 7]

[0054] Weigh 5000 g of magnesium dihydrogen phosphate and 1 g of phthalamide, mix them evenly to obtain solid powder. Heat the powder at 50° C. for 30 min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 448 nm, the phosphorescence lifetime is 0.52 s, the phosphorescence quantum yield can reach 11.91%, and it is easy to observe in a dark environment.

[0055] [Example 8]

[0056] Weigh 10000g of sodium dihydrogen phosphate and 1g of furan dicarboxamide, mix them evenly to obtain solid powder. Heat the powder at 500°C for 0.1min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 489nm, the phosphorescence lifetime is 0.41s, the phosphorescence quantum yield can reach 14.24%, and it is easy to observe in a dark environment.

[0057] [Example 9]

[0058] Weigh 1000g of calcium phosphate, 500g of terephthalic acid and 500g of terephthalic acid monoamide, and mix them evenly to obtain solid powder. Heat the powder at 50°C for 600min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 430nm, the phosphorescence lifetime is 0.17s, the phosphorescence quantum yield can reach 4.24%, and it can be observed in a dark environment.

[0059] [Example 10]

[0060] Weigh 1000 g of sodium monohydrogen phosphate and 20 g of furan dicarboxamide, mix them evenly to obtain solid powder. Heat the powder at 180° C. for 20 min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 489 nm, the phosphorescence lifetime is 0.45 s, the phosphorescence quantum yield can reach 15.36%, and it is easy to observe in a dark environment.

[0061] [Example 11]

[0062] Weigh 900 g of magnesium dihydrogen phosphate and 3 g of thiophene dicarboxamide, and mix them evenly to obtain a solid powder. Heat the powder at 260° C. for 5 min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 512 nm, the phosphorescence lifetime is 0.13 s, the phosphorescence quantum yield can reach 49.28%, and it is very easy to observe in a dark environment.

[0063] [Example 12]

[0064] Weigh 1000 g of aluminum dihydrogen phosphate and 20 g of thiophene dicarboxamide, mix them evenly to obtain solid powder. Heat the powder at 260° C. for 5 min and then cool it to room temperature to obtain the room temperature phosphorescent composite material. The emission wavelength is 430 nm, the phosphorescence lifetime is 0.06 s, the phosphorescence quantum yield can reach 10.39%, and it is easy to observe in a dark environment.

[0065] The delayed emission spectra of the room temperature phosphorescent composite materials prepared in the above Examples 1-12 are as follows: Figure 1 As shown, the spectra show the phosphorescence emission wavelength and phosphorescence quantum yield of Examples 1-12; the life decay curve comparison of the room temperature phosphorescent composite materials prepared in Examples 1-12 is shown in Figure 2 shown.

[0066]

Application Example 1

[0067] Weigh the room temperature phosphorescent composite material sample prepared in the above Example 1 and glass ionomer cement powder (whose main components are: 20 parts by mass of silicon oxide, 25 parts by mass of calcium fluoride, 13 parts by mass of sodium fluorosilicate, 23 parts by mass of aluminum oxide, 15 parts by mass of aluminum phosphate) at a mass ratio of 3:7 and mix them evenly. The mixture and glass ionomer cement liquid (whose main components are: 10 parts by mass of polyacrylic acid, 8 parts by mass of tartaric acid, 60 parts by mass of deionized water) are mixed evenly at a mass ratio of 2:1. Its compressive strength is 51.78MPa, and its phosphorescence quantum yield is 41.88%, which is very easy to observe in a dark environment. The clinical application has a clear boundary with natural teeth, and the specific effects are shown in Figure 3 The results of cytotoxicity tests showed that DRCs with different SMSED contents had no significant toxicity to cells when incubated for 1, 2, and 3 days, and the survival rates of the corresponding cells were all above 90%. Figure 6 .

[0068]

Application Example 2

[0069] The room temperature phosphorescent composite material sample prepared in the above Example 2 and glass ionomer cement powder (whose main components are: 25 parts by mass of silicon oxide, 20 parts by mass of calcium fluoride, 13 parts by mass of sodium fluorosilicate, 23 parts by mass of aluminum oxide, and 13 parts by mass of aluminum phosphate) are weighed and uniformly mixed at a mass ratio of 1:9, and the mixture is uniformly mixed with glass ionomer cement liquid (whose main components are: 30 parts by mass of polyacrylic acid, 8 parts by mass of tartaric acid, and 40 parts by mass of deionized water) at a mass ratio of 1:1. Its compressive strength is 59.65MPa, and the phosphorescence quantum yield is 16.64%, which is easy to observe in a dark environment.

[0070]

Application Example 3

[0071] The room temperature phosphorescent composite material sample prepared in the above-mentioned Example 3 and glass ionomer cement powder (whose main components are: 23 parts by mass of silicon oxide, 30 parts by mass of calcium fluoride, 10 parts by mass of sodium fluorosilicate, 23 parts by mass of aluminum oxide, 13 parts by mass of aluminum phosphate) are weighed and uniformly mixed at a mass ratio of 1:1, and the mixture is uniformly mixed with glass ionomer cement liquid (whose main components are: 20 parts by mass of polyacrylic acid, 5 parts by mass of tartaric acid, 40 parts by mass of deionized water) at a mass ratio of 2:1. Its compressive strength is 3.14MPa, and the phosphorescence quantum yield is 36.35%, which is very easy to observe in a dark environment.

[0072]

Application example 4

[0073] The room temperature phosphorescent composite material sample prepared in the above-mentioned embodiment 4 and glass ionomer cement powder (whose main components are: 23 parts by mass of silicon oxide, 25 parts by mass of calcium fluoride, 15 parts by mass of sodium fluorosilicate, 20 parts by mass of aluminum oxide, 13 parts by mass of aluminum phosphate) are weighed and uniformly mixed at a mass ratio of 29:1, and the mixture is uniformly mixed with glass ionomer cement liquid (whose main components are: 20 parts by mass of polyacrylic acid, 10 parts by mass of tartaric acid, 40 parts by mass of deionized water) at a mass ratio of 1:2. Its compressive strength is 1.30MPa, and the phosphorescence quantum yield is 44.50%, which is very easy to observe in a dark environment.

[0074]

Application Example 5

[0075] The room temperature phosphorescent composite material sample prepared in the above-mentioned Example 5 and glass ionomer cement powder (whose main components are: 23 parts by mass of silicon oxide, 25 parts by mass of calcium fluoride, 13 parts by mass of sodium fluorosilicate, 25 parts by mass of aluminum oxide, 10 parts by mass of aluminum phosphate) are weighed and uniformly mixed at a mass ratio of 1:29, and the mixture is uniformly mixed with glass ionomer cement liquid (whose main components are: 20 parts by mass of polyacrylic acid, 8 parts by mass of tartaric acid, 20 parts by mass of deionized water) at a mass ratio of 4:1. Its compressive strength is 65.37MPa, and the phosphorescence quantum yield is 6.68%, which can be observed in a dark environment.

[0076] Figure 4 The delayed emission spectra of the markable luminescent temporary sealing materials prepared in Application Examples 1-5 of the present invention are given, and the spectra show the phosphorescent emission wavelengths and phosphorescent quantum yields of Application Examples 1-5.

[0077] Figure 5 A mechanical property diagram of the markable luminescent temporary sealing material prepared in Application Examples 1-5 of the present invention is given, which shows the compressive strength of Application Examples 1-5.

Claims

1. An inorganic-organic room temperature phosphorescent composite material, characterized in that: The room temperature phosphorescent composite material is an inorganic-organic composite solid powder with room temperature phosphorescent properties, which is composed of phosphate and aromatic acid derivatives. The weight percentage of the aromatic acid derivatives ranges from 0.01% to 50%.

2. The room temperature phosphorescent composite material according to claim 1, characterized in that: The phosphate includes a phosphate main body and a hydrate composed of the phosphate main body.

3. The room temperature phosphorescent composite material according to claim 2, characterized in that: The phosphate body is composed of anions and cations, wherein the cations are one or more of the first, second, and third group metals, and the anions are H2PO4 - , or One or more of .

4. The room temperature phosphorescent composite material according to claim 1, characterized in that: The aromatic acid derivatives are one or more of the following aromatic acid derivatives: R1, R2, R3, R4 = OH, OR, NH2, NH-R, wherein the R group is a C1-C8 alkyl group.

5. A method for preparing the room temperature phosphorescent composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Weighing a phosphate and an aromatic acid derivative, and uniformly mixing them to obtain a precursor solid powder; (2) The room temperature phosphorescent composite material can be prepared by heating the precursor solid powder and then cooling it to room temperature.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the phosphate to the aromatic acid derivative is 1:1 to 10000:1, the heating temperature is 50° C. to 500° C., and the heating time is 0.1 min to 600 min.

7. Use of the room temperature phosphorescent composite material according to any one of claims 1 to 4, characterized in that: The application is to use the room temperature phosphorescent composite material as a characteristic luminescent material in a markable luminescent temporary sealing material.

8. The use according to claim 7, characterized in that: The application method comprises the following steps: (1) weighing a room temperature phosphorescent composite material and a glass ionomer cement powder, the main components of which are: 20 to 25 parts by weight of silicon oxide, 20 to 30 parts by weight of calcium fluoride, 10 to 15 parts by weight of sodium fluorosilicate, 20 to 25 parts by weight of aluminum oxide, and 10 to 15 parts by weight of aluminum phosphate, and uniformly mixing them to obtain a precursor solid powder; (2) Add glass ionomer cement liquid to the precursor solid powder, the main components of which are: 10 to 30 parts by weight of polyacrylic acid, 5 to 10 parts by weight of tartaric acid, and 20 to 60 parts by weight of deionized water, and mix well to obtain a markable luminescent temporary sealing material.

9. The use according to claim 8, characterized in that: The mass ratio of the room temperature phosphorescent composite material to the glass ionomer cement powder in step (1) is 1:29 to 29:

1.

10. The use according to claim 8, characterized in that: The mass ratio of the precursor solid powder to the glass ionomer cement liquid in step (2) is 1:2 to 4:1.

Citation Information

Patent Citations

  • Markable light-emitting repair material for dentistry, preparation method , binder, preparation method, and repair structure

    CN112426367A